Three-Way Stopcock as Breathing Circuit in Anesthetic Procedures on Wistar Rats as Animal Models in Research - Wardhana, Ardyan; Nugroho, Johanes (Indonesian Journal of Anesthesiology and Reanimation, 2022)
Introduction: General anesthesia in experimental animals is not limited in the field of anesthesia research. In Indonesia, ventilators and breathing circuit systems utilized in research involving anesthesia in rats are not widely available. The limitations in using ventilators and breathing circuit systems in research are one of the reasons why Indonesia is lacking complex and advanced animal experimental studies. Objective: This study aimed to examine a general anesthesia procedure for intubation in rats using tools and materials commonly discovered in clinical settings. Method: A search on the PubMed database using keywords consisting of animal study, rats, anesthesia, breathing circuit was performed. Review and Discussion: An endotracheal tube insertion procedure may utilize a Miller size 0 laryngoscope, while the endotracheal tube may use a 16 G intravenous cannula in which the needle is replaced by a small wire. The 3-way stopcock system may be considered as a replacement for the Mapleson E system for the breathing circuit system. The Fresh Gas Flow (FGF) source needs to be connected to the angled port, while the other two ports are connected to the reservoir and the intravenous cannula which would be delivered to the experimental animals. FGF three to five times as much as the minute ventilation may be used and the use of a reservoir capacity is similar to the tidal volume of spontaneous ventilation. Therefore, the oxygen flow rate is set to approximately 1-1.5 L per minute. A reservoir is not required for controlled ventilation. Conclusion: The use of a 3-way stopcock as a non-rebreathing circuit system is effective because it utilizes the similar principle as Mapleson E. The ability to use common tools and materials for general anesthesia procedures would significantly boost research of animal models in Indonesia to a further level.